PRINSIP KEMANFAATAN PENYELESAIAN SENGKETA ELEKTRONIK SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA TRANSAKSI PERDAGANGAN ELEKTRONIK - Ayudya Rizqi Rachmawati; Rahmadi Indra Tektona; Dyah Ochtorina Susanti (Departemen Hukum Perdata, 2020)
The research is motivated by the need for eff ective, effi cient and low-cost dispute resolution in dispute arising from electronic commerce transactions. That is because the implementation of electronic commerce transaction ha the characteristic of speed and ease, then it must also be accommodated in the process of settling the dispute. This study aims to analyze, and provide a description of the form of application principle of utilities in ODR as an alternative dispute resolution of electronic commerce user. The result of this normative legal research which uses statute and conseptual approach provide an explaination that online dispute resolution as an e-commerce alternative dispute resolution system trial has been in accordance with the principle of utilities, because to fulfi ll an element that there are in principle utilities in the analysis on law and economic.